(untitled) (Revista da Faculdade de Odontologia - UPF, 2025)
Titanium implants represent successful alternatives for bone and dental replacement in healthy patients. Modifications on the surface can increase their bioactivity and bone regeneration, with a consequent impact on the implant survival rate, and the modification technique used can impact the cellular response. The aim of this study was to characterized titanium surfaces modified by the cathodic polarization method with different current densities and exposure times. Seventy-two blocks of pretreated pure titanium were used and randomly allocated in four experimental groups, being 18 samples for group. The cathodic polarization process was conducted in a solution of acetic acid and sodium acetate (pH 3), being the titanium specimens used as cathode and a rectangular platinum as anode at a controlled temperature of 22°C. The current densities were 1.6 mA/cm2 and 4.5 mA/cm2 and the exposure times were 2h and 4h. Samples were dried and maintained in a Nitrogen vacuum chamber. The modified titanium samples were topographically characterized using Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM) and Energy Dispersion X-Ray Spectroscopy (EDX). Water contact angles formed in the surface of the titanium were measured with a tensiometer (ThetaLite TL101; Biolin Scientific Inc., Finland) using the sessile drop method, in four different times in minutes: t=0, t=15, t=30 and t=45. The contact angle formed between the water droplet and the surface was monitored in real time for 60 seconds. AFM and SEM analysis showed rougher surfaces in the modified groups. EDX data revealed the presence of sodium, carbon, and titanium mainly. The Wettability test indicated that all groups showed contact angles with less than 90°. The Control Group and Group 3 showed higher contact angles, around 76° to 71° and Groups 1 and 2 lower contact angles, around 66° to 63° respectively. The topography analysis showed higher roughness in the groups with higher current density and exposure time. The electrochemical cathodic polarization technique modified the titanium surfaces, as current density and exposure time influenced the roughness and wettability of the treated titanium surface, properties that could enhance osseointegration.